2011
DOI: 10.1002/stem.613
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Aldehyde Dehydrogenase Bright Stem and Progenitor Cell Populations from Normal Tissues: Characteristics, Activities, and Emerging Uses in Regenerative Medicine

Abstract: Flow cytometry has been used to detect cells that express high levels of the aldehyde dehydrogenase activity in normal tissues. Such ALDH bright (ALDHbr) cell populations have been sorted from human cord blood, bone marrow, mobilized peripheral blood, skeletal muscle, and breast tissue and from the rodent brain, pancreas, and prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 55 publications
4
99
0
5
Order By: Relevance
“…1). As expected (1,2), the transcriptional level of ALDH1A1 was also highly upregulated in CD34 + CD38 − cells (Fig. 1).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…1). As expected (1,2), the transcriptional level of ALDH1A1 was also highly upregulated in CD34 + CD38 − cells (Fig. 1).…”
Section: Resultssupporting
confidence: 81%
“…ALDH1 also is a marker for stem cells from most other tissues, and its expression decreases as stem cells differentiate (2). Although ALDH1's precise function in stem-cell biology is unclear, the major biologic function of the ALDH1 family appears to be the biosynthesis of retinoic acid (RA), the active metabolite of vitamin A (retinol) (3).…”
mentioning
confidence: 99%
“…Several workers have now reported that ALDHbr cells have higher stem cell activity than ALDHdim cells bearing similar surface antigens associated with stem cell activity [18]. Retinoid mediated regulatory changes have recently been shown to alter the ability of CD34 + cells in the peripheral circulation of coronary artery disease patients to home to ischemic tissue [48], a finding consistent with the idea that retinoids produced by ALDH play an important role in controlling the ability of stem cells to respond to ischemic damage.…”
Section: Discussionmentioning
confidence: 64%
“…None of the other ALDH isozymes that generate retinoic acids were expressed by these cells. Expression of only one ALDH1 subfamily isozyme that can oxidize retinoids appears to be a general characteristic of ALDHbr cells isolated by sorting with the BAAA substrate [18]. Retinoid oxidizing ALDH isozymes have a large substrate passage that permits bulky aldehyde substrates like retinoids and BAAA access to the catalytic site, while isozymes that oxidize small metabolic aldehyde substrates exclude such bulky substrates [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation